The Effect of Co2 Emission and Economic Growth on Energy Consumption in Sub Sahara Africa - Kareem, Salami Dada; Olusegun, Atoyebi Kehinde; Samuel, Olabode Oluwayinka (International Journal of Sustainable Energy and Environmental Research, 2017)
The relationship among CO2 emission, Economic Growth and Energy Consumption were examine in this study. This study specifically examines the combine impact CO2 emission, and Economic Growth on Energy Consumption. The study uses a dynamic panel data of esteem the time series analysis on 1980. Our result shows that Economic Growth is positively related to Energy Consumption. But when CO2 emission is interacted with Economic Growth the combine impact is increasing in energy consumption. The study therefore recommend that appropriate policy should formulated by the government to drive up energy consumption.